Bioaccessibility and bioactive potential of different phytochemical classes from nutraceuticals and functional foods - Nicolescu, Alexandru; Babotă, Mihai; Barros, Lillian; Rocchetti, Gabriele; Lucini, Luigi; Tanase, Corneliu; Mocan, Andrei; Bunea, Claudiu I.; Crișan, Gianina (Frontiers in Nutrition, 2023)
Nutraceuticals and functional foods are composed of especially complex matrices, with polyphenols, carotenoids, minerals, and vitamins, among others, being the main classes of phytochemicals involved in their bioactivities. Despite their wide use, further investigations are needed to certify the proper release of these phytochemicals into the gastrointestinal medium, where the bioaccessibility assay is one of the most frequently used method. The aim of this review was to gather and describe different methods that can be used to assess the bioaccessibility of nutraceuticals and functional foods, along with the most important factors that can impact this process. The link between simulated digestion testing of phytochemicals and their in vitro bioactivity is also discussed, with a special focus on the potential of developing nutraceuticals and functional foods from simple plant materials. The bioactive potential of certain classes of phytochemicals from nutraceuticals and functional foods is susceptible to different variations during the bioaccessibility assessment, with different factors contributing to this variability, namely the chemical composition and the nature of the matrix. Regardless of the high number of studies, the current methodology fails to assume correlations between bioaccessibility and bioactivity, and the findings of this review indicate a necessity for updated and standardized protocols.